Experimental characterization and Monte Carlo simulation of scintillator detectors in online electron FLASH radiotherapy dosimetry. (1st September 2022) - Morrocchi, Matteo; Pensavalle, Jake Harold; Ciarrocchi, Esther; Di Martino, Fabio; Felici, Giuseppe; Galante, Federica; Gasparini, Alessia; Grasso, Luigi; Linsalata, Stefania; Massa, Maurizio; Moggi, Andrea; Pacitti, Matteo; et al.
Abstract: Radiotherapy (RT) is a fundamental tool in cancer treatment. Recent technological advances improved considerably radiotherapy techniques, allowing to obtain more precise, effective and most importantly safer treatments. However, RT is not without risks. Ionizing radiation also injures healthy cells, and there is a limit to the amount of radiation an area of the body can safely receive over the course of a lifetime. A new delivery method, called FLASH radiotherapy (FLASH-RT) has shown very promising results in in vivo studies, where a significant increase in healthy tissue sparing (FLASH effect) was observed. FLASH-RT consists in delivering the ionizing radiation therapy at dose rates much higher than the ones used in conventional radiotherapy (CONV-RT). Because of the novelty of this method, every aspect of FLASH-RT is under study, such as how the FLASH effect depends on therapy delivery parameters and what exactly are the underlining biological mechanisms. Nonetheless, dosimetry presents a challenge to overcome. The high dose rates cause significant saturation problems which render standard dosimetric equipment inadequate. Therefore, the development of online (active) dosimeters is a priority. In the short term this technology enables more efficient measurements in the experimental context, since it gives immediate feedback. In the long term it provides the basis for future studies on dosimetry in clinical practice. In this work we show the construction and characterization of online FLASH dosimeters based on scintillator materials used in integrating-mode. A GEANT4 based Monte Carlo simulation code is specifically developed to calculate the medium-equivalence correction. The simulation is validated with experimental measurements obtained with a full-fledged FLASH linear accelerator, which produces electron pulsed beams at very high dose per pulse. Measurements suggest that the proposed dosimeters have a linear response in a wide range of dose per pulse values up to 6 Gy/p, while moderate saturation can be observed up to 12.5 Gy/p.